Magnetic ordering in a vanadium-organic coordination polymer using a pyrrolo[2, 3-d:5, 4-d′]bis(thiazole)-based ligand. Issue 63 (25th October 2018) - Getmanenko, Yulia A.; Mullins, Christopher S.; Nesterov, Vladimir N.; Lake, Stephanie; Risko, Chad; Johnston-Halperin, Ezekiel
Abstract : Here we present the synthesis and characterization of a hybrid vanadium-organic coordination polymer with robust magnetic order, a Curie temperature T C of ∼110 K, a coercive field of ∼5 Oe at 5 K. Abstract : Here we present the synthesis and characterization of a hybrid vanadium-organic coordination polymer with robust magnetic order, a Curie temperature T C of ∼110 K, a coercive field of ∼5 Oe at 5 K, and a maximum mass magnetization of about half that of the benchmark ferrimagnetic vanadium(tetracyanoethylene)∼2 (V·(TCNE)∼2 ). This material was prepared using a new tetracyano-substituted quinoidal organic small molecule7 based on a tricyclic heterocycle 4-hexyl-4 H -pyrrolo[2, 3- d :5, 4- d ′]bis(thiazole) (C6 -PBTz ). Single crystal X-ray diffraction of the 2, 6-diiodo derivative of the parentC6 -PBTz, showed a disordered hexyl chain and a nearly linear arrangement of the substituents in positions 2 and 6 of the tricyclic core. Density functional theory (DFT) calculations indicate thatC6 -PBTz -based ligand7 is a strong acceptor with an electron affinity larger than that of TCNE and several other ligands previously used in molecular magnets. This effect is due in part to the electron-deficient thiazole rings and extended delocalization of the frontier molecular orbitals. The ligand detailed in this study, a representative example of fused heterocycle aromatic cores with extended π conjugation, introduces new opportunities for structure–magnetic-property correlation studies where the chemistry of the tricyclic heterocycles can modulate the electronic properties and the substituent at the central N -position can vary the spatial characteristics of the magnetic polymer.